Optimalisasi Kinerja Proyek Konstruksi melalui Pendekatan Lean Construction di Manokwari - Natalia E Safkaur (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the optimization of school websites as information centers through the integration of alumni directories and organizational structures to enhance institutional communication and data management effectiveness. The research highlights that a well-structured website system not only functions as a medium for information dissemination but also as an integrated institutional database that supports digital-based governance in educational environments. The integration of alumni directories facilitates sustainable communication between schools and graduates, enabling stronger institutional networks and broader stakeholder engagement. The transparent presentation of organizational structures improves institutional accountability and accessibility of information for internal and external users. The synergy between these integrated features contributes to the development of an adaptive and responsive information system capable of supporting administrative needs and public communication. Ultimately, this implementation enhances the quality of educational information services and strengthens the institutional image in responding to the demands of digital transformation in the era of information technology.